Exploring pulmonary function and physical function in childhood cancer: A systematic review. (April 2021) - Ho, Simon; Betz, Gail; Marchese, Victoria
Graphical abstract: Highlights: Pulmonary function and physical function are often impaired in childhood cancer. Patients with pulmonary dysfunction are often asymptomatic. Physical function testing could unmask impairments undetectable by screening. There is a gap in the literature in diaphragm function in childhood cancer. Pulmonary function tests could be augmented by inspiratory muscle testing. Abstract: Background: Children with cancer experience pulmonary and physical function side effects from the cancer itself and the medical interventions. This systematic review examines the known relationship between pulmonary function and physical function in childhood cancer and identifies gaps in the literature. Methods: A search of Ovid Medline, CINAHL (EbscoHost) and Embase to identify literature from 2009 to March 2020. Results: Fifty-seven studies met inclusion criteria. Thirty-seven studies reported impaired pulmonary function. Incidence of pulmonary dysfunction ranged from 45.5 % to 84.1 %. Eighteen studies reported impaired physical function. Three studies investigated the relationship between pulmonary function and physical function. No studies explored inspiratory muscle strength. Conclusion: Pulmonary function and physical function are related and frequently impaired in children during and after cancer treatment. A literature gap was found in diaphragm function and its relationship with physical function. Future studies should focus on interventions that target the pulmonary mechanisms impacting physical function.